ESTETIKA TARI PIRING DALAM SALUANG DANGDUT DI NAGARI KUNCIR KABUPATEN SOLOK - Syaiyidatul Nur Fatimah; Erlinda Erlinda; Awerman Awerman (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT Piring dance in Kuncir village is a dance existed in Kuncir village, X Koto Diatas sub-district, Solok district, West Sumatra. Piring dance in Kuncir village can be danced by man or woman with the number of dancers is two until three dancers. The source of dance movement is related to human, nature and animal. Nowadays, the performance of Piring dance in Kuncir village has been performed together in the performance of Saluang Dangdut in Solok region. Factors that affected the aesthetics of Piring dance in the performance of Saluang Dangdut consisted of two factors namely internal factor including all artists’ creativities, choreography, local identity; and external factor. Reseach results revealed the form, social change and aesthetics found in the performance of Piring dance in Kuncir village and Piring dance in the performance of Saluang Dangdut. The aesthetic value of Piring dance in Kuncir village was reflected in the elements forming Piring dance in Kuncir village from the game played to the performance of Saluang Dangdut. Keywords: Aesthetics, Piring dance, Saluang Dangdut, Kuncir Village